High performance of solar panel based on new cooling and cleaning technique - Ahmed Khudhair Abbas; Kaleid Waleed Abed; Osama Ibrahim Abd; Yousif Al Mashhadany; Abdulrahman Hammad Jasim (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
There is a requirement for an elective wellspring of inexhaustible and earth feasible electrical vitality because of expanded power use and an unnatural weather change issues the world over. With the accumulation of dust and the surface temperature of cells or sun-based boards increase, their productivity drops significantly. Cooling and cleaning by using water can be utilized. Proteus and MikroC software have been used to simulate the model and write the code. In this paper, is design and an experimental study shrewd customized cleaning and cooling system for photo-voltaic (PV) modules installed in Ramadi, Iraq. Which is started dependent on low essentialness coming about due to dust accumulating and high temperature conditions. This was attempted by presenting two indistinct photovoltaic modules close to one another. The fundamental unit was equipped with a model of the cleaning structure while the resulting unit was seen as standard. An upgraded cleaning and cooling methodology are gotten with the data acquiring structure. An expansion in vitality profitability of 12.4% was acquired because of lessening the operational aggravations of residue amassing and warming of the board surface. The automatic cleaning mechanism used in the system reduces human stress by washing the PV panel with low energy use.